Practical English usage - Swan, Michael, 1936- ([Oxford, United Kingdom] : Oxford University Press, 2020)
Practical English Usage answers the questions that teachers and learners ask about English grammar and vocabulary, using clear corpus-informed explanations and examples.
Acknowledgements -- Introduction -- Contents overview -- Language terminology -- Phonetic alphabet -- Practical English usage -- Index.
Includes index.
Keywords: English language -- Usage; English language -- Grammar; English language -- Textbooks for foreign speakers -- English; English language; English language -- Grammar; English language -- Usage; Textbooks -- for English speakers; Textbooks